Intermedialità come Gesamtkunstwerk critico. Appunti sul visuale nella scrittura di W.G. Sebald - Tedesco, Salvatore (Scenari, 2021)
This work mean to analyze the intermedial strategies of W. G. Sebald, with specific reference to the first short and very intense tale of the volume Die Ausgewanderten, and to the game of references between literary text, photo-texts, cinema.